Role of the state in implementation of strategic investment projects: The SaHo Model for nuclear power - Łukasz Sawicki; Bozena Horbaczewska (International Journal of Management and Economics, 2021)
The purpose of the paper is to present an innovative business model, the SaHo Model, designed specifically to enable the Polish government to implement nuclear power development plans, which can be possibly used in other countries and in sectors requiring high capital expenditures. The SaHo Model solves the problems identified in the nuclear energy sector, which are related to high investment risk and high costs of capital at the investment stage, and ensures revenues after connection to the grid. Since the state is the investor at the initial stages, it takes over most of the risk in the short term. Selling the shares before connection to the grid, the state significantly reduces the financial involvement in the long term. From then on, the SaHo Model works similar to the Finnish Mankala or American electric cooperative models, producing and selling energy to their shareholders at production costs. None of the models used so far in nuclear energy provides such opportunities. The SaHo Model allows to enhance the competitiveness of the national industry and to increase public acceptance for nuclear power. Thus, it is not only a business model but also a concept for the functioning of the nuclear industry.
Keywords: G18; G31; Q48; 650; business model; nuclear power development